Sedimentation velocity analytical ultracentrifugation interacting systems - Schuck, Peter William 1968-; Zhao, Huaying (CRC Press, Taylor & Francis Group, 2018)
"Analytical ultracentrifugation is one of the most powerful solution techniques for the study of macromolecular interactions, to define the number and stoichiometry of complexes formed, and to measure affinities ranging from very strong to very weak and repulsive. Building on the data analysis tools described in the volume Sedimentation Velocity Analytical Ultracentrifugation: Discrete Species and Size-Distributions of Macromolecules and Particles, and the experimental and instrumental aspects in the first volume Basic Principles of Analytical Ultracentrifugation, the present volume Sedimentation Velocity Analytical Ultracentrifugation: Interacting Systems is devoted to the theory and practical data analysis of dynamically coupled sedimentation processes. Features: - The rich phenomenology of sedimenting interacting systems is systematically presented - A physical picture and mathematical framework is developed side-by-side - Strategies for practical data analysis are reviewed - Consequences for experimental design strategies are discussed - Cross-references to practical data analysis software - Provides extensive illustration of principles and examples The volume is designed to fill a gap in biophysical methodology to provide a framework that builds on the fundamentals of the highly developed traditional methods of analytical ultracentrifugation, updated with current methodology and from a viewpoint of modern applications. It is written for researchers and graduate students interested in the application of analytical ultracentrifugation for the study of interacting systems, such as biological macromolecules, multi-protein complexes, polymers, or nanoparticles"...
Includes bibliographical references (pages 245-267) and index
Keywords: Ultracentrifugation; Macromolecules -- Analysis; Nanoparticles -- Analysis; Sedimentation analysis